What is the Czech (Historical) Science Lacking? Response to a ‘Manifesto’ of Four Young Historians - Nešpor, Zdeněk R. (Dějiny – teorie – kritika, 2012)
In his contribution, the author adopts a stance with respect to views published in a critical essay by Pavel Baloun, Jan Gruber, Jan Mareš, and Vít Strobach, O výuce historie za kapitalismu a o mluvících hlavách (On Teaching History Under Capitalism and on Talking Heads; Dějiny – teorie – kritika 8/2012, p. 121-144). The text focuses mainly on explaining the function of the Grant Agency of the Czech Republic, whose evaluation mechanisms authors of the abovementioned article criticise. Th e author of this contribution also considers the degree to which the professionally established members of the Grant Agency can or may be criticised by young authors who cannot as yet present any comparable scientific achievements limitations and concludes by thoughts of ethics of science.